The nature of professional and relational self‐aspects at the goal and narrative levels of personality. (18th April 2014) - Dunlop, William L.; Walker, Lawrence J.; Wiens, Thomas K.
<x xml:space="preserve">Abstract</x> The self‐concept is constituted by a series of context‐specific self‐aspects. Researchers have considered the manner in which personality traits vary across these self‐aspects. Here, we examined self‐aspects corresponding to professional and relational contexts at the goal and narrative levels of personality. In each of two studies, participants provided lists of goals and recounted self‐defining narratives, corresponding to the aforementioned contexts. Goals and narratives were coded for themes of agency and communion. At both descriptive levels, agency more characterized the professional self‐aspect and communion, the relational self‐aspect. A consideration of context‐specific goals and narratives informs understanding regarding the nature of the self in its multifaceted form.